The Hen's Egg Test on Chorioallantoic Membrane: An Alternative Assay for the Assessment of the Irritating Effect of Vaccine Adjuvants. (November 2016) - Batista-Duharte, Alexander; Jorge Murillo, Gisela; Pérez, Ulpiano Marqués; Tur, Enieyis Naranjo; Portuondo, Deivys Fuentes; Martínez, Bruno Téllez; Téllez-Martínez, Damiana; Betancourt, Juan E.; Pérez, Oliver
Local reactions are the most frequent adverse event associated with vaccines. Adjuvants are major constituents of many vaccines and they are frequently involved in these reactions, associated with their irritating effect and the stimulation of local inflammation. The hen's egg test on chorioallantoic membrane (HET-CAM) is an alternative toxicological method widely used to determine ocular irritation potential, but very few studies have demonstrated the utility of this method for assessing the irritant properties of vaccine adjuvants. In this work, known/experimental adjuvants were evaluated by both HET-CAM and an in vivo local toxicity study in mice to compare irritation scores to determine whether there was a correlation (Pearson test). Based on these data ( r = 0.9034; P < 0.0001), the HET-CAM assay can be used as an alternate method for the prediction of the local toxicity potential of adjuvant candidates to be used in vaccines.